2016
DOI: 10.4103/2229-5178.193896
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous anaplastic large cell lymphoma masquerading as large pyogenic granuloma

Abstract: Primary cutaneous anaplastic large cell lymphoma (pcALCL) forms 9% of the cutaneous T-cell lymphomas. It usually presents as solitary reddish brown ulcerating nodule or indurated plaque. Sometimes, it mimics other dermatological diseases such as eczema, pyoderma gangrenosum, pyogenic granuloma, morphea, and squamous cell carcinoma. Our case presented with large pyogenic granuloma like lesion with regional lymphadenopathy. Since pcALCL is rare, one can misdiagnose such cases and therefore high index of suspicio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…1,2 A rich inflammatory background of neutrophils and eosinophils can be seen in some cases, giving rise to the so-called "pyogenic" variant, where the neoplastic infiltrate can be obscured by inflammatory cells. [4][5][6][7] In 1990, Chan et al 8 reported a case of ALCL with surrounding myxoid stroma, similar to that seen in malignant mesenchymal tumors. A subsequent lymph node biopsy showed a tumor composed of markedly atypical spindle cells reminiscent of the storiform pattern of an undifferentiated pleomorphic sarcoma.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…1,2 A rich inflammatory background of neutrophils and eosinophils can be seen in some cases, giving rise to the so-called "pyogenic" variant, where the neoplastic infiltrate can be obscured by inflammatory cells. [4][5][6][7] In 1990, Chan et al 8 reported a case of ALCL with surrounding myxoid stroma, similar to that seen in malignant mesenchymal tumors. A subsequent lymph node biopsy showed a tumor composed of markedly atypical spindle cells reminiscent of the storiform pattern of an undifferentiated pleomorphic sarcoma.…”
mentioning
confidence: 87%
“…The presence of cells with “reniform” or “semilunar” nuclei (classic “hallmark” cells) is also typical of C-ALCL and systemic anaplastic large-cell lymphoma (ALCL) 1,2. A rich inflammatory background of neutrophils and eosinophils can be seen in some cases, giving rise to the so-called “pyogenic” variant, where the neoplastic infiltrate can be obscured by inflammatory cells 4–7…”
mentioning
confidence: 99%
“…These lesions are true Kaposi sarcomas, not PG [ 32 ]. Other malignancies that can mimic PC are malignant lymphomas, basal cell carcinoma, or malignant melanoma [ 33 - 35 ]. In immunocompromised patients, deep soft tissue infections like phaeohyphomycosis or bartonellosis should be considered [ 36 , 37 ].…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…Cutaneous manifestations of ALCL have been noted in the literature to mimic dermatologic conditions such as eczema, pyoderma gangrenosum, and squamous cell carcinoma [ 17 ]. Luo et al [ 2 ] reported a case of ALK-negative ALCL presenting as Behcet's disease, with recurrent penile and oral ulcers initially treated with steroids without improvement and later diagnosed 4 weeks later with penile tissue biopsy.…”
Section: Discussionmentioning
confidence: 99%